Decoding Cellular Landscapes: Unravelling Periodontitis and Periapical Periodontitis at the Single-Cell Frontier - Yuan Li; Jun Wang; Yu Zhang; Dengke Li; Wuyang Zhang; Xuebing Li; Bolun Zhang; Kaijin Hu; Jianfei Yan; Yang Xue (International Dental Journal, 2025)
Objective: Elucidate differences in key gene expression and cellular heterogeneity in alveolar bone between periodontitis (PD) and periapical periodontitis (PP) by analysing single-cell RNA sequencing data. Methods: Single-cell RNA sequencing datasets for PD (GSE171213) and PP (GSE181688) were obtained from the Gene Expression Omnibus and analysed. Differentially expressed genes were identified in comparisons of PD versus healthy controls (HC), PP versus HC, and PD versus PP. Functional enrichment analyses were performed to explore heterogeneity. Key genes related to angiogenesis (ARGs), inflammation (IRGs), and phagocytosis (PRGs) were identified and combined to form PD-specific and PP-specific key gene sets. The expression of these key genes was validated by quantitative real-time polymerase chain reaction. Cell types were annotated using SingleR, and key cell types were further analysed for their proportions, intercellular communication, and gene expression patterns. Hallmark pathway analysis and cell cycle/differentiation assessments were conducted to understand functional heterogeneity. Results: A total of 251 Differentially expressed genes associated with humoral immunity, B cell regulation, and leukocyte/lymphocyte activation were identified. Four PD-specific and 16 PP-specific key genes were found, and fibroblasts and macrophages were identified as the two key cell types. Fibroblast interactions were prominent, and cells in the G1 phase predominated. The key genes were highly expressed during early T cell and macrophage differentiation and during late fibroblast and plasma cell differentiation. Expression levels of these genes were highest in PP, intermediate in PD, and lowest in HC. Conclusion: This study identified four PD-specific and 16 PP-specific key genes, as well as two pivotal cell types in alveolar bone inflammatory diseases. Investigating the functional diversity of these cell types could enhance insights into the pathogenesis of these conditions. Clinical Relevance: The findings may guide clinical treatment strategies for alveolar bone involvement in PD and PP, and lay a theoretical foundation for exploring the underlying inflammatory mechanisms.